EFEKTIVITAS PENGGUNAAN APLIKASI BJB DIGI PADA ASN DI KOTA BANDUNG - Giovani, Nazwa Salsabilla; Abubakar, Rodlial Ramdhan Tackbir; Pradesa, Hafid Aditya; Novira, Alikha (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study aims to analyze the effectiveness of the DIGI mobile banking application by Bank BJB among Civil Servants (ASN) in Bandung City. To measure the success of the information system, the IS Success Model developed by DeLone and McLean is utilized, which includes four main dimensions: system quality, information quality, user satisfaction, and net benefits. The research employs a quantitative approach through the distribution of questionnaires to 143 ASN respondents who use the BJB DIGI application. The results indicate that both system quality and information quality have a significant influence on user satisfaction, which in turn affects the perceived net benefits. Based on these findings, the study recommends feature development, improvements in information clarity, and enhanced user support services.